Effect of Work Motivation with Working Discipline in Nursing Performance in Special Unit X Hospital in Yogyakarta - Sri Tungga Dewi; Tri Pitara Mahanggoro; Mariska Urmila (Universitas Muhammadiyah Yogyakarta, 2018)
The research was conducted at X hospital which aims to determine the effect of work motivation, work discipline on the performance of nurses in the inpatient room. The data obtained has been analyzed using descriptive analysis and quantitative analysis. Quantitative analysis used multiple regression analysis to determine the effect of independent variables on the dependent variable, but before the test is carry out the validity and reliability has been tasted, sampling was using total sampling technique where the population is equal to the number of samples as many as 47 nurses. The results of the study revealed that work motivation factors had a significant effect on the performance of nurses in X hospital, while the discipline factors did not have a significant effect on the performance of nurses of X hospital while the influence of work motivation and work discipline on performance shows a positive number which means there is an influence on performance. The results of the study revealed that motivation factors had a significant effect on performance as (0.041) which means that h0 was rejected and h1 was accepted. While the results of work discipline on performance did not have a significant effect, value of the discipline as (0.750) where the value is bigger than the standard value of error (0.05) which means h0 was accepted and h1 was rejected. From the research, it was found that the human resources at X hospital were still lacking in terms of motivation and in terms of work discipline the quality of human resources had improved.